A novel saturation calculation model of fractured-vuggy carbonate reservoir via multiscale pore networks: a case study from Sichuan Basin, China. (1st February 2021) - Sun, Jianmeng; Chi, Peng; Cheng, Zhigang; Yang, Lin; Yan, Weichao; Cui, Likai
Abstract: Existing saturation models cannot effectively describe the specific fractured-vuggy carbonate reservoir in area A of the Sichuan Basin, southwestern China. This reservoir has got a wide pore size distribution, strong heterogeneity, high gas saturation and complex electrical conductivity mechanism. Hence, the present study attempted to establish a new saturation calculation equation for this carbonate reservoir based on the microscopic conductivity mechanism of the rock. Here, we first used the multiscale computed tomography (CT) scanning method to build multiscale digital rocks. Subsequently, we applied the maximum sphere algorithm to extract the pore space structure and constructed the multiscale pore network models. By using the cross-scale fusion method, four different pore configurations were determined. Then, the percolation theory was implemented to simulate the conductivity mechanism of the constructed pore network models. As a result, the fluid distribution characteristics and the resistivity variation trends of the different pore structures were obtained. The simulation results showed that the fracture system of the studied reservoir had a much greater effect than the vug system on the carbonate rock's electrical conductivity, and the conductivity was closely related to the fluid distribution. In addition, based on the simulation results, a new conductivity model was proposed that incorporates the coupling phenomenon of pores, vugs and fractures; and also a new saturation calculation equation for triple-porosity media was established. The observations indicated that the field application of the proposed equation had an acceptable performance with an error value of less than 2.56%. The results from the present study provide new insights into the evolution of electrical properties in triple-porosity carbonate systems.